Mediating effect of HRM Practices on lean management and operational performance; A conceptual framework - Azhani, Ismail; Yuserrie, Zainuddin (The Turkish Online Journal of Design, Art and Communication, 2018)
Public sectors in Malaysia are operating in a rapidly-changing world. The emergence of globalization, the borderless world and increasing budgetary constraints are major challenges to the public sectors in ensuring continuous improvement in service delivery to customers. This paper presents a conceptual framework with the major objective to investigate from the resource-based view theory perspective, the mediating effect of human resource management practices on the relationship between lean management and operational performance within Malaysia public sector. The main research question addresses by this study is whether lean management enhances operational performance directly or indirectly through the support of the human resource management practices. The conceptual model could build momentum by stimulating new research in public sector which is anticipated to be a framework for future studies in the academic field and public sector lean management implementers.